Evaluating the Efficacy of Subantimicrobial Dose of Doxycycline in the Treatment of Periodontal Disease as Host Modulation - Jaafer , Samer Salim; Alasady , Mukhalled Salim; Hanfoosh , Hayder Saad (American Journal of Biomedicine and Pharmacy, 2025)
Periodontal disease is a chronic inflammatory condition where host-mediated tissue destruction plays a central role, and conventional therapies like scaling and root planing (SRP) often fail to fully address the underlying immune response. Despite evidence supporting host modulation therapy, the effectiveness of subantimicrobial dose doxycycline (SDD) in routine clinical settings remains under-investigated. This randomized, double-blind, placebo-controlled clinical trial evaluated 60 patients with moderate to severe chronic periodontitis, comparing outcomes between SRP combined with SDD versus SRP alone. Clinical parameters—probing depth, attachment level, and bleeding on probing—were assessed at baseline, 3 months, and 6 months. The study demonstrated that SDD significantly enhanced periodontal outcomes without notable adverse events. These findings support the integration of SDD as a safe and effective adjunct to SRP, offering a targeted approach to modulate the host response and potentially reduce the need for invasive surgical interventions in periodontal therapy.